Pediatric Eye Examination: An Overview - Siddharth Baindur; Siddharth Madan; Aparna Soman; Umesh Sharma; Meghna Sethi; Kashish Garg; Chitra Ogio; Anju Rastogi (Delhi Journal of Ophthalmology)
The comprehensive pediatric eye and vision examination helps in the evaluation of the structure, function, and health of the eyes and visual system. The parent/caregiver should accompany the child into the examination room for making the examination of a child easier. During the examination, information that is obtained is collated to explain symptoms reported by the patient and/or parent/caregiver and diagnose their cause. A comprehensive pediatric eye examination provides the means to identify the presence of other ocular or systemic conditions that may exist with or without symptoms.